Biologic disease modifying anti-rheumatic treatment effects on cardiac geometry and function in collagen-induced arthritis - Le Roux, Regina (My University, 2020)
Chronic systemic inflammation significantly increases the risk of heart failure. Diastolic dysfunction is a preclinical disorder that frequently develops into heart failure with a reduced ejection fraction and is particularly prevalent in persons exposed to high-grade inflammation, including rheumatoid arthritis (RA). Inflammation has been directly linked to the development of diastolic dysfunction. In the RA population, disease progression is dramatically reduced when treatment is aimed at inflammation, using biologic antirheumatic drugs, including tumor necrosis factor alpha (TNF-α) inhibitors and interleukin 6 (IL-6) receptor blockers. However, the effect of these drugs on cardiac geometry and function needs further elucidation. The aim of our study was to determine the effect of biologic disease modifying anti-rheumatic drugs (DMARDs) on cardiac geometry and function in a collagen induced arthritis (CIA) rat model. Seventy-eight male and female Sprague Dawley rats were randomly divided into four groups, namely an untreated control group, an inflammation group, a TNF-α inhibitor group and an IL-6 receptor blocker group. Inflammation was induced by a 0.2 ml subcutaneous injection of Bovine Type II collagen blended into incomplete Freund’s adjuvant at the base of the tail, in all groups except the control group. Following the onset of inflammation, the TNF-α group received 10 mg/kg of Enbrel every third day for six weeks and the IL-6 group received 8mg/kg of Actemra once a week for six weeks. Arthritis scores and body weights were measured weekly and blood pressure were measured every two weeks throughout the study. Following six weeks of drug treatment, cardiac geometry and function were measured using echocardiography and inflammatory cytokine concentrations (C-reactive protein, TNF-α, IL-6) were determined using enzyme-linked immunosorbent assays (ELISAs). Changes in body weight, arthritis scores and blood pressure were determined by repeated measures analysis of variance (ANOVA). Differences in inflammatory markers and echocardiography variables were determined by two-way ANOVA followed by Tukey post-hoc tests. Body weight and blood pressure did not change during the intervention in any of the groups (all p > 0.05). The inflammation and IL-6 group had a significantly greater interventricular iv septal thickness (IVST) and posterior wall thickness (PWT) in diastole, as well as an increased relative wall thickness (RWT) compared to controls (p < 0.05 for all). The TNFα treatment group had significantly smaller IVST and PWT in diastole and RWT compared to the inflammation group (p < 0.001, p = 0.004 and p = 0.001, respectively). However, no differences were recorded in any systolic function markers (ejection fraction, stroke volume or fractional shortening) between groups (all p > 0.05). Diastolic function was significantly reduced in all groups exposed to inflammation. Lateral mitral annular velocity (e’) was lower in the inflammation (3.8 ± 0.1 cm/s; p = 0.001), TNF-α (3.5 ± 0.2 cm/s; p < 0.001) and IL-6 (3.7 ± 0.2 cm/s; p < 0.001) groups, compared to the control group (4.5 ± 0.1 cm/s). Filling pressure (E/e’) was higher in the inflammation (29.9 ± 1.2; p = 0.02), TNF-α (32.5 ± 1.5; p = 0.001) and IL-6 (29.9 ± 1.7; p = 0.048) groups compared to the control group (24.9 ± 1.2). The TNF-α group additionally showed an increased E/A, and decreased lateral wall e’/a’, compared to the inflammation group (p = 0.02 and p = 0.03, respectively). Inflammatory cytokine concentrations were strongly associated with changes in RWT (CRP: r = 0.48; p < 0.0001, TNF-α: r = 0.45; p < 0.0001, IL-6: r = 0.36; p = 0.001), IVST in diastole (CRP: r = 0.43; p = 0.001, TNF-α: r = 0.50; p < 0.001, IL-6: r = 0.32; p = 0.01) and PWT in diastole (CRP: r = 0.44; p < 0.001, TNF-α: r = 0.48; p < 0.001, IL-6: r = 0.34; p = 0.003). These associations remained significant even after adjusting for body weight and sex. Changes in diastolic function was not consistently related to inflammatory markers. In conclusion, exposure to inflammation adversely affected cardiac remodelling and diastolic function in a CIA rat model. TNF-α inhibition was protective against cardiac remodelling but not against changes in diastolic function. IL-6 receptor blockade did not protect against inflammation-induced cardiac geometry or function changes. Further investigation is required to underpin the exact mechanisms whereby inflammation affects cardiac geometry and function.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020